Predictors of survival stratification in patients with wild-type cardiac amyloidosis - Siepen, Fabian aus dem; Bauer, Ralf; Voß, Andreas; Hein, Selina; Aurich, Matthias; Riffel, Johannes; Mereles, Derliz; Buß, Sebastian Johannes; Katus, Hugo; Kristen, Arnt (Clinical research in cardiology, 2018)
ObjectivesTo analyze clinical predictors of mortality in wild-type transthyretin amyloidosis (wt-ATTR).MethodsIn total, 191 patients (73.8 ± 0.5 years; 176 males, 15 females) with histologically proven wt-ATTR amyloidosis and genetic exclusion of a transthyretin gene variant were included. Comprehensive clinical characteristics, ECG, biomarkers, and echocardiography were analyzed retrospectively. Strain analyses were performed offline using TomTec Imaging Systems, Germany. Univariable and multivariable analyses predicting all-cause mortality were carried out.ResultsPatients presented with significant heart failure (NYHA 2.5 ± 0.8; NT-proBNP 3644 (4981) pg/ml; LV ejection fraction 45.8 ± 15.0%). LogNT-proBNP correlated with indicators of disease severity. Similar results were obtained for basal and midventricular, but not apical longitudinal strain. During median follow-up of 26.2 ± 1.7 months 46 (25.5%) patients died (40 males, 23%; six females, 40%). In female patients 1-/2-year survival was lower [92.9/67.7%; median survival 30.6 (21.1-40.1) months] when compared to male patients [96.5%/86.6%; median survival 63.9 (45.8-82.0) months]. Parameters associated with survival were NT-proBNP, NYHA class, heart rate, midventricular longitudinal strain, mitral annular plane systolic excursion (MAPSE), Karnofsky Index, systolic blood pressure, estimated glomerular filtration rate. Multivariable analysis revealed MAPSE and NT-proBNP as independent predictors of mortality in the whole cohort and midventricular strain in the subgroup of patients in sinus rhythm.ConclusionsNo sex-specific bias was observed between male and female patients with wt-ATTR regarding age at onset and morphological characteristics. Multivariable analysis revealed MAPSE and NT-proBNP as independent predictors of survival in the whole cohort, whereas midventricular longitudinal strain was the only independent predictor in patients in sinus rhythm.